The Influence of Health Education about the Benefits of Breast Milk on Mother's Motivation in Exclusively Breast Feeding Infants - Yulia Safitri; Pratiwi Syah Putri; Maimunah R (Science Midwifery, 2022)
Exclusive breastfeeding is highly recommended for infants aged 0 to 6 months, because breast milk contains complete nutrition for infant growth and development. But currently the coverage of breastfeeding is still low because the motivation of mothers to give exclusive breastfeeding is also low which is suspected because of the lack of health education about the benefits of breastfeeding. The purpose of this study was to determine the effect of health education about the benefits of breastfeeding on mother's motivation in giving exclusive breastfeeding. This study is an analytical study using a one group pre and posttest design approach with a quasi-experimental design. The study was conducted in Klinik Pratama Hadijah. The study population was 30 people and all were sampled. Data analysis was done by univariate and bivariate using paired sample t-test at a confidence level of 95% ( = 0.05). It is recommended to nurses to provide health education or education to every mother who visits the Klinik Pratama Hadijah. by using a language that is easily understood and understood by the mother so she is motivated to give exclusive breastfeeding to her baby.